Faktor-Faktor yang Mempengaruhi Peningkatan Kinerja Pendamping Program Keluarga Harapan - Walahe, Dewi (Gorontalo Journal of Public Administration Studies, 2019)
This article aims to find out the factors that influence the improvement of the family of hope program in Tapa Subdistrict, Bone Bolango District. This article uses a qualitative approach, the writer also functions as the main instrument that plunges the field and tries to collect data through observation and interviews and interviews. In drawing conclusions the author uses the inductive method to draw events from the data that has been collected that can be generalized, then clearly this inductive method to assess empirical facts that are found and then matched with existing theories.The results of this paper show that communication is very important in achieving the goals of the Implementation of the Family Hope Program in Tapa District. Effective implementation occurs when decision makers already know what they are going to do. The knowledge they will do can work well if the communication goes well. So the implementation of the program must be well communicated to the parties concerned. Furthermore the resource factor also has a very important influence. The availability of resources in implementing a program is one factor that must always be considered. In this case the resources in question are human resources, financial resources, and time resources to support the implementation of the family of hope program in the District of Tapa. Furthermore, one of the factors influencing the effectiveness of policy implementation is the attitude of the implementor.  Arikel ini bertujuan untuk mengetahui faktor-faktor yang mempengaruhi peningkatan program keluarga harapan di Kecamatan Tapa Kabupaten Bone Bolango. Artikel ini menggunakan pendekatan kualitatif, penulis sekaligus berfungsi sebagai instrument utama yang terjun kelapangan serta berusaha sendiri mengumpulkan data melalui observasi maupun wawancara dan interview. Hasil dari tulisan ini menunjukkan bahwa Komunikasi sangat menetukan keberhasilan pencapaian tujuan dari Implementasi Program Keluarga Harapan di Kecamatan Tapa. Implementasi yang efektif terjadi apabila para pembuat keputusan sudah menengetahui apa yang akan mereka kerjakan. Pengetahuan yang akan mereka kerjakan dapat berjalan dengan baik bila komunikasi berjalan dengan baik. Sehingga implementasi program harus dikomunikasikan dengan baik kepada pihak pihak yang terkait. Lebih lanjut faktor sumberdaya juga mempunyai pengaruh yang sangat penting. Ketersediaan sumberdaya dalam melaksanakan sebuah program merupakan salah satu faktor yang harus selalu diperhatikan.